Globalizatoin and decentralization: emerging issues from the Indian experience - Tandon, B.B.; Ramachandran, H.; Agnihotri, V.K. (2001)
This article attempts to describe briefly: (1) the contents of the economic reforms and issues arising out of them that impact of decentralization and administration; (2) the basic features of decentralization and its impact on administration; and (3) the basic approach to administrative reforms that are on the anvil. The larger blueprint for change, both in administration and decentralization, is yet to be developed; meanwhile a number of reactive changes are being brought about. Therefore, the approach in this article is to capture the process of ongoing changes in the arena of decentralization and administration through illustrative examples. These, after all, are the felt needs and the building blocks of the evolving framework.
Keywords: Decentralization - India; Globalization - India; Decentralization